From Peasant to Patriarch: Account of the Birth, Upbringing, and Life of His Holiness Nikon, Patriarch of Moscow and All Russia - Shusherin, Ioann (Lexington Books, 2007)
Nikon (1605-1681), patriarch of Moscow and all Russia, is best known for imposing the religious reforms that ultimately led to the schism of the Russian Orthodox Church. Yet only the Account of Birth, Life, and Upbringing of His Holiness Nikon, Patriarch of Moscow and All Russia (1680s), comes close to immortalizing the vicissitudes of Nikon's entire life. Written by Ioann Shusherin's (d. 1693), the patriarch's protZgZ and confidant, the Account presents Nikon as he appeared to his contemporary supporters. The biography chronicles Nikon's steady rise through the ecclesiastical ranks, dramatic downfall, and extraordinary rehabilitation. While discussing Nikonian religious reforms, the Account focuses on Nikon's relationship with the Romanov royal family and his monastery building program, especially the early history of the New Jerusalem Monastery and its main sanctuary, the Church of the Resurrection. This unique narrative features rare eyewitness accounts of momentous and daily life during a period of unprecedented political, religious, and social change in Russia. From Peasant to Patriarch is the first English language translation of the Account. Dr. Kevin Kain and Dr. Katia Levintova offer extensive commentary, parallel texts, and a glossary of Russian terms that contribute to the depth of this text. From Peasant to Patriarch opens new doors to the study of Russian history, religion, and culture.